Reasons Behind Non-Exclusive Breastfeeding by Working Women in Mataram City West Nusa Tenggara - Haryani; Luh Putu Lila Wulandari; I Nyoman Mangku Karmaya (Public Health and Preventive Medicine Archive, 2014)
Background and purpose: The purpose of this study was to determine why working mothers choose to not exclusively breast feed their infants in Mataram, West Nusa Tenggara. Methods: The study used a qualitative design with a phenomenological approach. Data collection in this study involved focus group discussions and in-depth interviews. In-depth interviews with 9 working women not exclusively breastfeeding. Focus group discussions two comprising of 21 respondents were husbands, in-laws, mother’s family, healthcare provider, workplace representatives, religious and community leaders. Result: Study findings indicated that the primary reason for working women to not exclusively breastfeed, because of a lack of individual motivation, pressures of a high workload, lack of permitted time off, lack of infrastructure and concerns about losing employment due to time off. Obstacles included fear of losing employment, maternal physical factors (low/no milk production), psychological factors (stress/anxiety/frustration), lack of facilities and supporting infrastructure. Conclusion: The predominant reasons behind non-exclusive breastfeeding were lack of personal motivation, high workload, lack of permitted time off, lack of supporting infrastructure and fear of losing employment. The external obstacles for providing exclusive breastfeeding were economic factors, the mother’s ability to produce milk, psychological factors, lack of supporting infrastructure.